DESIGN OF CLOUD-BASED CHATBOT APPLICATION AT PT. TRAVELOKA SINGAPORE USING THE AGILE METHOD - Pratama, Yuda Adi; Kristiana, Titin (Jurnal Pilar Nusa Mandiri, 2023)
The role of customer service will be good if it can serve all obstacles or difficulties users face directly and in real time. However, there are times when the number of customer service is not proportional to the number of users who make complaints to customer service, and often, users ask questions generally available on Frequent Ask Questions (FAQ), so there are limitations and are fewer responsive in serving user complaints. By developing a cloud computing-based Chatbot application, it is hoped that it will make it easier for customer service to handle recurring questions and increase response time to users in real-time. The development of this chatbot application uses the agile method with the scrum framework. Where in the development process carried out is divided into several phases called sprints. The development of this application was carried out in 3 sprints from the time the project was announced to completion.